Effect of race and ethnicity on utilization and outcomes of assisted reproductive technology in the USA - Alice J. Shapiro; Sarah K. Darmon; David H. Barad; David F. Albertini; Norbert Gleicher; Vitaly A. Kushnir (BMC, 2017)
Abstract Background The purpose of this study was to determine the utilization and live birth rates of assisted reproductive technology (ART) modalities among various racial and ethnic groups in recent years. Methods We reviewed ART data reported to the Society for Assisted Reproductive Technologies Clinic Outcome Reporting System (SART CORS) for autologous ART and third-party ART (3ART) cycles which involved donor oocytes, sperm, embryos and gestational carrier, performed in the U.S. between 2004 and 2013. To gauge demand by various racial/ethnic groups for ART services, we examined fertility rates and demographics of the entire U.S. birth cohort over the same time interval. Results Of 1,132,844 autologous ART cycles 335,462 resulted in a live birth (29.6%). An additional, 217,030 3ART cycles resulted in 86,063 live births (39.7%). Hispanic and Black women demonstrated high fertility and lower utilization rates of autologous ART and 3ART. Caucasian and Asian women exhibited lower fertility rates and higher autologous ART and 3ART utilization. Autologous ART resulted in higher live birth rates among Caucasian and Hispanic women and lower rates among Asian and especially Black women. 3ART improved live birth rates in all races/ethnicities, though Black women experienced lower live birth rates with most modalities. Spontaneous abortion rates were higher among Black women following autologous ART and some 3ART modalities than those among Caucasian women. Conclusion Utilization of ART is inversely related to fertility rates. Autologous ART produces lower live birth rates among Asian and Black women. 3ART results in relatively low live birth rates among Black women. Trial registration SART CORS #57 , Registered 5/14/2015